2021
DOI: 10.1038/s41467-021-24900-4
|View full text |Cite
|
Sign up to set email alerts
|

Endo-lysosomal Aβ concentration and pH trigger formation of Aβ oligomers that potently induce Tau missorting

Abstract: Amyloid-β peptide (Aβ) forms metastable oligomers >50 kDa, termed AβOs, that are more effective than Aβ amyloid fibrils at triggering Alzheimer’s disease-related processes such as synaptic dysfunction and Tau pathology, including Tau mislocalization. In neurons, Aβ accumulates in endo-lysosomal vesicles at low pH. Here, we show that the rate of AβO assembly is accelerated 8,000-fold upon pH reduction from extracellular to endo-lysosomal pH, at the expense of amyloid fibril formation. The pH-induced promotio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 78 publications
4
57
0
1
Order By: Relevance
“…By using the WT7 cell line, the effects of Z640 on APP processing and Aβ generation was assessed. Consistent with previous reports ( 33 , 34 ), Aβ oligomers treatment promoted APP processing towards the β-cleavage pathway and therefore increased both CTF-β and Aβ generation. Following treatment with 10 µM Z640 it was found that although Z640 alone could not induce significant changes in full-length APP and APP-CTFβ, it could significantly increase the expression of APP-CTFα and the ratio of APP-CTFα/APP-CTFβ ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…By using the WT7 cell line, the effects of Z640 on APP processing and Aβ generation was assessed. Consistent with previous reports ( 33 , 34 ), Aβ oligomers treatment promoted APP processing towards the β-cleavage pathway and therefore increased both CTF-β and Aβ generation. Following treatment with 10 µM Z640 it was found that although Z640 alone could not induce significant changes in full-length APP and APP-CTFβ, it could significantly increase the expression of APP-CTFα and the ratio of APP-CTFα/APP-CTFβ ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…Biochemical analysis of brain extracts revealed that TREM2 deficiency or the expression of the NHD associated T66M in APP transgenic mice increased the levels of pSer8-Aβ in form of oligomeric assemblies. Aβ oligomers exert neurotoxicity, and oligomer levels correlate with neuronal dysfunction in AD [ 3 , 21 , 50 , 56 , 57 , 62 , 80 ]. Aβ oligomers also seed fibrillization and promote the deposition in form of extracellular plaques [ 6 , 10 , 20 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aβ oligomers also seed fibrillization and promote the deposition in form of extracellular plaques [ 6 , 10 , 20 , 32 ]. In addition, oligomers can be internalized by neurons resulting in Aβ accumulation within neurons [ 2 , 9 , 13 , 56 , 60 ]. Since TREM2 has been shown to selectively bind oligomeric assemblies of Aβ and promote microglial uptake [ 31 , 44 , 72 , 82 ], the loss of TREM2 function could result in decreased clearance of oligomers and thereby lead to increased uptake by neurons, and deposition in extracellular plaques and the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the aforementioned targets, many emerging targets show potential as indicators for pathological alterations in AD, and are yet to be further investigated in amyloidosis animal models, such as 1) metal dysregulation and copper trafficking e.g. using [ 64 Cu]GTSM [208]; 2) reactive oxygen species [209] and pH alterations [210]; 3) microtubule using [ 11 [214][215][216]: 5) mitochondria imaging using [ 18 F]BCPP-EF [217]; and 6) Glycogen Synthase Kinase-3 imaging using [ 11 C]2, [ 11 C]OCM-44, [ 3 H]PF-367 [218,219].…”
Section: Discussionmentioning
confidence: 99%